The Contemplative Bridge: Reimagining Collaboration between Religion and Bioclimate Science - Beaudette, J. A. (Lumen et Vita, 2022)
In a time of climate upheaval and rapid biodiversity loss, theoretical collaborations between religion and science may already be too late. The time of ecological transition is upon us. Scientists recognize that to make measurable impacts, approaches to the practice of science require new vision. Today, conservation ecologists are beginning to integrate contemplative principles into scientific practices and policies, such as mindfulness, empathy, and deep listening. Research suggests that contemplative approaches can improve scientific processes, enrich cross-cultural dialogue, and facilitate measuring environmental outcomes. Contemplative encounters can also obscure normative boundaries between scientific discovery and theological inquiry, evoking questions about Divine Nature beyond name and form. Drawing on conservation research and theological scholarship, this paper presents contemplation as a constructive bridge between religion and science, one that holds great promise for meaningful collaboration.